Glycerol conversion by aerobic granular sludge. (1st December 2022) - Elahinik, Ali; Haarsma, Maureen; Abbas, Ben; Pabst, Martin; Xevgenos, Dimitrios; van Loosdrecht, Mark C.M.; Pronk, Mario
Highlights: Glycerol can be used as cheap carbon source in wastewater treatment plants Glycerol-EBPR with a collaboration among Tessaracoccus & Ca. Accumulibacter Glycerol fermented to propionate Stoichiometric evaluation of the anaerobic conversions Stable granulation and EBPR is possible with glycerol Abstract: Glycerol is abundantly present in wastewater from industries such as biodiesel production facilities. Glycerol is also a potential carbon source for microbes that are involved in wastewater nutrient removal processes. The conversion of glycerol in biological phosphorus removal of aerobic granular sludge processes has not been explored to date. The current study describes glycerol utilization by aerobic granular sludge and enhanced biological phosphorus removal (EBPR). Robust granules with good phosphorus removal capabilities were formed in an aerobic granular sludge sequencing batch reactor fed with glycerol. The interaction between the fermentative conversion of glycerol and product uptake by polyphosphate accumulating organisms (PAO) was studied using stoichiometric and microbial community analysis. Metagenomic, metaproteomic and microscopic analysis identified a community dominated by Actinobacteria ( Tessaracoccus and Micropruina) and a typical PAO known as Ca . Accumulibacter. Glycerol uptake facilitator (glpF) and glycerol kinase (glpK), two proteins involved in the transport of glycerol into the cellular metabolism, were only observed in the genome of the Actinobacteria. The anaerobic conversion appeared to be a combination of a substrate fermentation and product uptake-type reaction. Initially, glycerol fermentation led mainly to the production of 1, 3-propanediol (1, 3-PDO) which was not taken up under anaerobic conditions. Despite the aerobic conversion of 1, 3-PDO stable granulation was observed. Over time, 1, 3-PDO production decreased and complete anaerobic COD uptake was observed. The results demonstrate that glycerol-containing wastewater can effectively be treated by the aerobic granular sludge process and that fermentative and polyphosphate accumulating organisms can form a food chain in glycerol-based EBPR processes. Graphical Abstract: Image, graphical abstract